Effects of postexercise sauna bathing on recovery of swim performance - Skorski, S.; Schimpchen, J.; Pfeiffer, M.; Ferrauti, A.; Kellmann, M.; Meyer, T. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Despite indications of positive effects of sauna (SAU) interventions, effects on performance recovery are unknown. The aim of the current study was to investigate acute effects of SAU bathing after an intensive training session on recovery of swim performance. Methods: In total, 20 competitive swimmers and triathletes (3 female and 17 male) with a minimum of 2 y of competition experience (national level or higher) participated in the study. Athletes completed an intensive training session followed by either a SAU bathing intervention or a placebo (PLAC) condition in a randomized order. SAU consisted of 3?×?8 min of SAU bathing at 80-85°C, whereas during PLAC, athletes applied a deidentified, pH-balanced massage oil while passively resting in a seated position. Prior to training, swimmers conducted a 4×50-m all-out swim test that was repeated on the following morning. Furthermore, subjective ratings of fatigue and recovery were measured. Results: Swimmers performed significantly worse after SAU (4×50-m pre-post difference: +1.69 s) than after PLAC (-0.66 s; P=.02), with the most pronounced decrease in the first 50 m (P=.04; +2.7%). Overall performance of 15 athletes deteriorated (+2.6 s). The subjective feeling of stress was significantly higher after SAU than after PLAC (P=.03). Conclusion: Based on published findings, the smallest substantial change in swimming performance is an increase in time of more than 1.2 s; thus, the observed reductions appear relevant for competitive swimmers. According to the current results, coaches and athletes should be careful with postexercise SAU if high-intensity training and/or competitions are scheduled on the following day.